The Impact of 3 Years of Targeted Indoor Residual Spraying With Pirimiphos-Methyl on Malaria Parasite Prevalence in a High-Transmission Area of Northern Zambia. Issue 12 (7th May 2019) - Hast, Marisa A; Chaponda, Mike; Muleba, Mbanga; Kabuya, Jean-Bertin; Lupiya, James; Kobayashi, Tamaki; Shields, Timothy; Lessler, Justin; Mulenga, Modest; Stevenson, Jennifer C; Norris, Douglas E; Moss, William J
Abstract: Malaria transmission in northern Zambia has increased in the past decade, despite malaria control activities. Evidence-based intervention strategies are needed to effectively reduce malaria transmission. Zambia's National Malaria Control Centre conducted targeted indoor residual spraying (IRS) in Nchelenge District, Luapula Province, from 2014 to 2016 using the organophosphate insecticide pirimiphos-methyl. An evaluation of the IRS campaign was conducted by the Southern Africa International Centers of Excellence for Malaria Research using actively detected malaria cases in bimonthly household surveys carried out from April 2012 to July 2017. Changes in malaria parasite prevalence after IRS were assessed by season using Poisson regression models with robust standard errors, controlling for clustering of participants in households and demographic, geographical, and climatological covariates. In targeted areas, parasite prevalence declined approximately 25% during the rainy season following IRS with pirimiphos-methyl but did not decline during the dry season or in the overall study area. Within targeted areas, parasite prevalence declined in unsprayed households, suggesting both direct and indirect effects of IRS. The moderate decrease in parasite prevalence within sprayed areas indicates that IRS with pirimiphos-methyl is an effective malaria control measure, but a more comprehensive package of interventions is needed to effectively reduce the malaria burden in this setting.